Post-capitalist property. Issue 3 (2nd October 2017) - Ireland, Paddy; Meng, Gaofeng
Abstract: When writing about property and property rights in his imagined post-capitalist society of the future, Marx seemed to envisage 'individual property' co-existing with 'socialized property' in the means of production. As the social and political consequences of faltering growth and increasing inequality, debt and insecurity gradually manifest themselves, and with automation and artificial intelligence lurking in the wings, the future of capitalism, at least in its current form, looks increasingly uncertain. With this, the question of what property and property rights might look like in the future, in a potentially post-capitalist society, is becoming ever more pertinent. Is the choice simply between private property and markets, and public (state-owned) property and planning? Or can individual and social property in the (same) means of production co-exist, as Marx suggested? This paper explores ways in which they might, through an examination of the Chinese household responsibility system (HRS) and the 'fuzzy' and seemingly confusing regime of land ownership that it instituted. It examines the HRS against the backdrop of Marx's ideas about property and subsequent (post-Marx) theorizing about the legal nature of property in which property has come widely to be conceptualized not as a single, unitary 'ownership' right to a thing (or, indeed, as the thing itself) but as a 'bundle of rights'. The bundle-of-rights idea of property, it suggests, enables us to see not only that 'individual' and 'socialized' property' in the (same) means of production might indeed co-exist, but that the range of institutional possibility is far greater than that between capitalism and socialism/communism as traditionally conceived.